(untitled) (Eurasian Medical Research Periodical, 2025)
This article will consider issues of cost control and optimization in sanatorium-wellness institutions. The author gave an important definition of the role of internal audit in optimizing costs and increasing overall efficiency in the institution. The costs were analyzed by type and special attention was paid to the effective use of Information Technology in the process of their control, Also, methods of cost optimization, strategies of internal audit and its practical results are covered and discussed with examples.